Petrarca per stillicidio - Usher, Jonathan (Cuadernos de Filología Italiana, 2005)
Petrarch’s influence in Britain, if, via traditional literary histories, we look only at great figures, is essentially fragmentary and ambiguous. If, on the other hand, we burrow, by electronic means, into the cultural hinterland of the intense contemporary discussions surrounding the Reformation, we find a Petrarch who offers protestants of varying backgrounds a series of propaganda coups not only on general moral issues, but also on the current question of married clergy. The Petrarch thus revealed is a Latin one, but not a humanist.